If (gx) = 2x^2 -3x, evaluate, expand and simplify completely. g(-2) g(-c) g(d^2) g(-2)
Last edited by batman123; Mar 5th 2006 at 03:01 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by batman123 If (gx) = 2^2 -3x, evaluate, expand and simplify completely. g(-2) g(-c) g(d^2) g(-2) I hope you mean g(x)=2^2-3x or g(x)=4-3x g(-2) is just plugging in -2 for x. So we get g(-2)=4-3(-2)=16 g(-c) is the same thing. Plug in -c for x, and see what you get.
Originally Posted by batman123 If (gx) = 2x^2 -3x, evaluate, expand and simplify completely. g(-2) g(-c) g(d^2) g(-2) Hello, first: The last problem is the same as the first problem, so I'll not do that again. second: Plug in the given value for x and calculate: Greetings EB
View Tag Cloud